Description of Aedes sp Mosquito Population Density Based on Ovitrap Index in Babadan Hamlet Sukoharjo - Kristina Army; Fina Laila Rahma; Revana Putri Santoso; Dwi Haryatmi (Jurnal Biologi Tropis, 2026)
Dengue Hemorrhagic Fever (DHF) remains a public health concern in endemic areas, where vector density determines transmission risk. This descriptive cross-sectional study aimed to determine the population density of Aedes sp.. mosquitoes based on the Ovitrap Index (OI) in Babadan Hamlet, Sukoharjo Regency. A total of 40 ovitraps were installed indoors for seven days and examined microscopically for egg detection. Larvae were morphologically identified, and adult mosquitoes were collected using the sweeping method for genus identification. The results showed that 2 ovitraps were positive for Aedes eggs, resulting in an OI of 5% (low density category). Larvae were detected in 25% of ovitraps. Adult mosquito identification revealed Aedes aegypti (100%) as the only species found, while Aedes albopictus was not detected. In conclusion, although the OI indicates low vector density, the presence of larvae and adult Aedes aegypti suggests a continued risk of DHF transmission. These findings emphasize the need for sustained vector surveillance and community-based control strategies to prevent dengue outbreaks.